Los Altos apricots. - Gordon, John C. (photographer):::Creator::::::::::::
Workers with wooden crates of Los Altos apricots. The crates read: "Ripened on the tree. Los Altos apricots. Grown and shipped by the Los Altos orchards of Los Altos, Santa Clara County, California."